Uji Aktivitas Diuretik Ekstrak Etanol Kombinasi Daun Putri Malu (Mimosa pudica L.) dan Daun Pacar Kuku (Lawsonia inermis L.) pada Tikus Jantan Galur Wistar - Dwi Novita Eka Sari; Fransiska Leviana; Kisrini Kisrini (Fakultas Farmasi Universitas Setia Budi, 2014)
Putri malu (Mimosa pudica L.) and pacar kuku (Laswonia inermis L.) leaves can be used as diuretic agent. This research aimed to find out the diuretic effect of combination of putri malu and pacar kuku leaves ethanol extract as the effective dose on Wistar male rat. The tested animal used consisted of 35 rats, divided into 7 groups: furosemida positive control (1,44 mg/200 g BW), negative control CMC 0.5%, extract of putri malu leaves (20 mg/200 g BW), extract of pacar kuku leaves (50 mg/200 g BW), combination of putri malu and pacar kuku leaves ethanol extract (10 : 25 mg/200 g BW; 5 : 37,5 mg/200 g BW; 15 : 12,5 mg/200 g BW). Observation was conducted every hour for 6 hours, and then at 12 and 24 hours. The diuretic effect was obtained by estimating cumulative urine volume and AUC (Area Under The Curve). The data was processed using oneway variance analysis followed by Tukey HSD test. The result of research the combination of putri malu and pacar kuku leaves ethanol extract has a diuretic effect. The extract combination had diuretic effect higher than the single extract. The combination of putri malu and pacar kuku leaves ethanol extract dose of 5 mg/200 g BW : 37,5 mg/200 g BW and 15 mg/200 g BW : 12,5 mg/200 g BB had diuretic activity compatible to the positive control.